Cataract Surgery in High Hyperopia - Waldmann, Nicolas Philipp; Gerber, Nadine; Hill, Warren; Goldblum, David (Klinische Monatsblätter für Augenheilkunde, 2018)
Background Although cataract surgery is a well-established and standardised procedure, it can be demanding and associated with higher complication rates in high hyperopia. We present clinical data for highly hyperopic patients who underwent cataract surgery over a 12-year period (2005 – 2016) and at a single centre.Patients and Methods Out of a total of 11 434 cataract operations, 41 highly hyperopic eyes (SN60AT ≥ 31 dpt) were included for analysis. We compared the target spherical equivalent to the final postoperative spherical equivalent for five different formulas. We also reviewed the best corrected distance visual acuity (BCDVA) before and after surgery and any complications.Results LogMAR BCDVA increased significantly from a mean of 0.5 before to 0.37 after surgery (p = 0.02). The main reasons for the reduced final BCDVA were glaucoma, Fuchs corneal endothelial dystrophy, and age-related macular degeneration. One eye suffered a radial capsule tear and received a sulcus implanted intraocular lens (IOL). There was no statistically significant difference between formulas with respect to aberration of the final spherical equivalent.Conclusions Patients with high hyperopia often have ocular comorbidities. Such eyes may be surgically challenging, resulting in reduced benefits from cataract surgery compared to normal eyes.
Keywords: cataract surgery; high hyperopia; biometry; SN60AT